1993
DOI: 10.1016/0014-5793(93)80053-w
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of cDNA encoding the fire ant venom protein Sol i II

Abstract: For the first time the cDNA encoding a fire ant venom protein has been sequenced. Oligonucleotides were designed according to the amino acid sequence. The cDNA sequence was obtained by hybridizing these primers to mRNA and enhancement by the PCR technique. Comparison to the amino acid sequence of the venom protein shows a leader sequence 19 amino acids long.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…This result obviously indicated that spots A and B are different proteins; therefore, the protein in spot A was Sol gem 3, whereas the protein in spot B was Sol gem 2. These MS results The amino acid residues at the N-terminus of Sol gem 2 were determined to be ANEELKIIRK, a sequence that has 80% identity with that of the N-terminus of Sol i 2 (24,38). This result indicated that Sol gem 2 most likely shares high homology with allergen Sol i 2.…”
Section: Page Analysis and Protein Identification Of Crude Venommentioning
confidence: 82%
See 1 more Smart Citation
“…This result obviously indicated that spots A and B are different proteins; therefore, the protein in spot A was Sol gem 3, whereas the protein in spot B was Sol gem 2. These MS results The amino acid residues at the N-terminus of Sol gem 2 were determined to be ANEELKIIRK, a sequence that has 80% identity with that of the N-terminus of Sol i 2 (24,38). This result indicated that Sol gem 2 most likely shares high homology with allergen Sol i 2.…”
Section: Page Analysis and Protein Identification Of Crude Venommentioning
confidence: 82%
“…Under reducing condition (Figure 2, lane 4), the Sol gem 2 band co-migrated with the Sol gem 4 band, suggesting that these two proteins might have similar structures. Sol i 2 and Sol i 4 are members of a unique protein family (3,38,39). Sol i 4 is structurally related to Sol i 2, with 118 amino acids and no carbohydrate modifications (40).…”
Section: Page Analysis and Protein Identification Of Crude Venommentioning
confidence: 99%
“…3,5 The primers used are shown in Table I. The mRNA was isolated by using the Promega (Madison, Wis) polyATtract system.…”
Section: Cloning Of the Phospholipasementioning
confidence: 99%
“…The primary sequences of these allergens have been determined by both amino acid sequencing 2 and cDNA cloning. 3,4 Sol i 3 is a member of the antigen 5 family. 2,5,6 Sol i 2, 3, and 4 have all been expressed by insect cells in immunoreactive form.…”
mentioning
confidence: 99%
“…The first step in producing recombinant allergens can utilize any of several strategies including IgE immunoscreening of expression cDNA libraries [20, 21], phage display with immunoscreening [22, 23, 24, 25, 26]or DNA-based techniques such as reverse transcriptase-polymerase chain reaction (RT-PCR) which requires the determination of a partial amino acid sequence of the natural allergen or closely related protein [27, 28, 29, 30]. RT-PCR methods are particularly advantageous if the IgE-binding activity is dependent on posttranslational modifications, or if only a limited supply of specific IgE is available, and it also allows the isolation of multiple isoforms simultaneously [29, 31, 32, 33, 34, 35].…”
Section: Introductionmentioning
confidence: 99%